Preface - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 1997)
This collection of articles is devoted to the important current issues of education science. The collection consists of articles focusing on the topics of comparative and historical pedagogy, school management and hodegetics.